The Architecture of Creek Road Market and the Image of Port Harcourt Metropolis, Rivers State, Nigeria - Ebikiemo K.W; T. Lawson; Imaah N.O; Pepple T.D (International Journal of Urban Design and Development, 2025)
Marketplaces are seen as centers of attraction in every city. Therefore, the architecture of marketplaces should be given extensive attention to attract a positive image of the city. If the architecture of a market lacks functionality, it will affect the perception of the city. Often, market designers ignore the key users of the market space and focus on providing profit-oriented spaces. This leads to the spillover of trading activities by the key users, who are mostly petty traders. The disorderliness experienced from the spillover of trading activities often gives a negative image of the city. The spillover of trading activities to the market environment usually leads to certain hostility in the environment. This is the current state of the subject of study, “Creek Road Market,” located in Rivers State, Nigeria. The government of Rivers State, to save the image of the city, has tried several times to curb the act of this spill without any result. Some studies have been conducted concerning the issues caused as a result of the spillover; however, the possible architectural issues that may be associated with the spillover have not been considered. Therefore, this research tends to investigate the issues connected with the architecture of the Creek Road Market, leading to the spillover of trading activities into the environment. To investigate this, the architecture of the Creek Road Market was identified, and the issues associated with the architecture were examined. A mixed-method approach was used for this study. Data was gathered through questionnaires, interviews, and personal observations. The findings from both quantitative and qualitative data reveal space inadequacy to accommodate all traders as the major reason for the spillover in the Creek Road Market. Further reasons include inadequate visibility of goods and insufficient space to accommodate traders’ goods.
Keywords: Architecture; Creek Road Market; Environment; Port Harcourt Metropolis; image of the city; issues; spill out; traders